2015
DOI: 10.1111/ijpp.12215
|View full text |Cite
|
Sign up to set email alerts
|

How glaucoma patient characteristics, self-efficacy and patient–provider communication are associated with eye drop technique

Abstract: Objectives The objective of this study was to examine the extent to which patient characteristics, eye drop technique self-efficacy, and ophthalmologist–patient communication about eye drop administration are associated with glaucoma patients’ ability to instil a single drop, have the drop land in the eye, and avoid touching the applicator tip of the medication bottle to the eye or face while self-administering eye drops. Methods Glaucoma patients (n = 279) were recruited from six ophthalmology clinics. Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 19 publications
0
27
0
2
Order By: Relevance
“…Therefore, regular reevaluation of administration skills and patient education seems necessary to continuously assure and improve administration skills and to prevent relapse into previous administration patterns. [2, 2830] In addition, errors persisted in some patients throughout the follow-up visits probably requiring additional education materials (e.g., videos[27]) or further error prevention strategies that go beyond patient education (e.g., helping aids[31] or support by a caregiver[32]). Therefore, further studies should identify patient characteristics that predict the capability to improve eye-drop administration skills through education to allow for more evidence-based recommendations on patient education for correct eye-drop administration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, regular reevaluation of administration skills and patient education seems necessary to continuously assure and improve administration skills and to prevent relapse into previous administration patterns. [2, 2830] In addition, errors persisted in some patients throughout the follow-up visits probably requiring additional education materials (e.g., videos[27]) or further error prevention strategies that go beyond patient education (e.g., helping aids[31] or support by a caregiver[32]). Therefore, further studies should identify patient characteristics that predict the capability to improve eye-drop administration skills through education to allow for more evidence-based recommendations on patient education for correct eye-drop administration.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of preparedness and apparent difficulties with eye drop administration is not confined to parents who need to instil drops into the eyes of their young children; adult patients also have difficulty administering their own topical ophthalmic medications (2,9) and providers rarely instruct them on how to instil their eye drops (4). Additionally it has been noted that not all of the adult patients who report successful instillation of drops actually achieve this in reality, there is an apparent mismatch between subjective perceptions of performance and observation of successful technique (1).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Adults frequently have difficulty instilling eye drops in their own eyes (1), and this can be observed even in patients who report no difficulties in self-administration of drops (2). Examples of poor techniques include touching of the eye or ocular adnexa with the bottle, poor handling or squeezing of the eye drop container, difficulty aiming at the eyes, dispensing multiple drops and needing multiple attempts before successful instillation (3,4). The challenges of administering eye drops to children is further exacerbated by their poorer understanding and cooperation, but little is known about the difficulties experienced by parents when administering eye drops to their young children.…”
Section: Introductionmentioning
confidence: 99%
“…Female gender, younger age, lack of education, living alone, and severe eye disease were all found to correlate with improper technique and inferior adherence to the regimen. [ 2 3 4 5 ] The Chennai Glaucoma Study (2009) found that, in addition to a high incidence of cataracts, locals lacked awareness of ocular health. [ 6 ] Proper use of medication is a high priority in areas like Chennai, India, that are vulnerable to eye disease and infection.…”
mentioning
confidence: 99%
“…Administration was assessed using a validated protocol for analyzing eyedrop instillation. [ 2 ] The interview was scored out of a possible eight. Sociodemographic factors (age, gender, education, residence, poverty score, administration by self/other, previous use) were analyzed for association with understanding the prescribed regimen and proper instillation.…”
mentioning
confidence: 99%